Multidrug-resistant urinary tract isolates of Escherichia coli from Ribeirão Preto, São Paulo, Brazil - Santo, Edilene [UNESP]; Salvador, Miriam Mendonça; Marin, José Moacir (FapUNIFESP (SciELO), 2007)
Multiple resistances to antimicrobial drugs arising in Escherichia coli isolates may complicate therapeutic management of urinary tract infection (UTI) by this organism. In order to assess the multidrug resistance (MDR) among urinary E. coli isolates, we have tested 11 antimicrobial drugs against 67 isolates from outpatients attended in a tertiary-care teaching hospital and of 78 isolates from a municipal health unit, respectively in Ribeirão Preto, State of São Paulo, Brazil. Seventy-six percent and 22% of the isolates from the tertiary-care hospital and the municipal unit, respectively, were resistant to three or more different classes of agents, and were considered to present MDR. Among the isolates from the hospital patients, 73.0%, 65.0%, 58.0%, 58.0% and 31.0% were resistant to tetracycline, ampicillin, cephalothin, trimethoprim-sulfamethoxazole (TMP/SMX) and norfloxacin, respectively; resistance from the municipal unit patients were 31.0%, 37.0%, 8.0%, 29.0% and 12.0% respectively, to the same drugs. The predominant phenotype among the MDR isolates presented is ampicillin, TMP/SMX and tetracycline resistance. The high prevalence of drug resistance among UTI patients calls for continuous surveillance to assure effective control of this infection. © 2007 by The Brazilian Journal of Infectious Diseases and Contexto Publishing. All rights reserved.
Keywords: Antimicrobial susceptibility; Escherichia coli; Multidrug-resistance; Urinary tract infections; ampicillin; cefalotin; cefoxitin; ceftriaxone; cefuroxime; cotrimoxazole; gentamicin; nitrofurantoin; norfloxacin; tetracycline; tobramycin; adolescent; adult; antibiotic resistance; antibiotic sensitivity; bacterium isolate; Brazil; child; clinical article; concentration response; female; human; infant; infection control; male; multidrug resistance; outpatient; phenotype; tertiary health care; urinary tract infection; Adolescent; Adult; Anti-Bacterial Agents; Child; Child, Preschool; Drug Resistance, Multiple; Escherichia coli Infections; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Phenotype; Urinary Tract Infections